2020
DOI: 10.3390/su12208576
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Governance, Social Bonds and Information Security Policy Compliance: A Perspective towards Oil and Gas Employees

Abstract: Information security attacks on oil and gas (O&G) organizations have increased since the last decade. From 2015 to 2019, almost 70 percent of O&G organizations faced at least one significant security breach worldwide. Research has shown that 43 percent of security attacks on O&G organizations occur due to the non-compliant behavior of O&G employees towards information security policy. The existing literature provides multiple solutions for technical security controls of O&G organizations. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 79 publications
1
25
0
Order By: Relevance
“…Process eco-innovation demonstrated that a cleaner production process can be incorporated into the industrial manufacturing process without negotiating sustainability, societal development, and most importantly the circular economy [39][40][41][42]. Cleaner production is an approach that accumulates various production factors such as shortening the greenhouse emission force, water concentration, waste concentration, energy application, and reprocessing or recycling the materials [38][39][40][41]43].…”
Section: Model-2 Proactive Process Eco-innovation and Firm Financial Performancementioning
confidence: 99%
“…Process eco-innovation demonstrated that a cleaner production process can be incorporated into the industrial manufacturing process without negotiating sustainability, societal development, and most importantly the circular economy [39][40][41][42]. Cleaner production is an approach that accumulates various production factors such as shortening the greenhouse emission force, water concentration, waste concentration, energy application, and reprocessing or recycling the materials [38][39][40][41]43].…”
Section: Model-2 Proactive Process Eco-innovation and Firm Financial Performancementioning
confidence: 99%
“…The study results proved that social factors (i.e., rules-oriented ethical climate and susceptibility) could weaken the effect of the command and control and self-regulatory approaches of ISPC on an individual and organizational level. An empirical study [3] examined organizational governance and social bond factors' effects on ISPC. The study results proved that an organization with good organizational governance could enhance social bonding among employees, improving the ISPC in the organizational context.…”
Section: Authorsmentioning
confidence: 99%
“…Research shows that about 70% of incidents happened due to human negligence (intentional or unintentional). A study on security professionals' behavior concluded that 43% of data breaches are due to employees' behavior [3,4]. In 2014 IBM cybersecurity intelligence index reported almost 95% of information security incidents to involve employee negligence [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, O&G organizations have geographically disparate sites, which needs secure communication to enable efficiency and effectiveness in decision making and production processes. Although the O&G industry is rapidly moving towards digitization and automation, the management and governance infrastructure of the O&G industry are still prone to many risks, including internal [3,4] , external, physical, reputational, and cybersecurity risks. A small disruption in IT and operation technology (OT) can cause very large financial and reputational losses to O&G organizations [5].…”
Section: Introductionmentioning
confidence: 99%